2020
DOI: 10.1038/s41598-020-66196-2
|View full text |Cite
|
Sign up to set email alerts
|

Using eye movements to detect visual field loss: a pragmatic assessment using simulated scotoma

Abstract: Glaucoma is a leading cause of irreversible sight-loss and has been shown to affect natural eyemovements. These changes may provide a cheap and easy-to-obtain biomarker for improving disease detection. Here, we investigated whether these changes are large enough to be clinically useful. We used a gaze-contingent simulated visual field (VF) loss paradigm, in which participants experienced a variable magnitude of simulated VF loss based on longitudinal data from a real glaucoma patient (thereby controlling for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…It is well established that eye movements are affected by either real or simulated glaucomatous visual field defects. [9][10][11][12][22][23][24][25] However, previous studies were conducted at different sampling frequencies, and there is no evidence to suggest which sampling frequency and eye movement parameters are best suited for screening glaucomatous VFL during a free-viewing task. This study aimed to demonstrate how the sampling frequency of eye trackers influenced eye movement parameters in distinguishing glaucomatous visual field defects from those in healthy eyes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that eye movements are affected by either real or simulated glaucomatous visual field defects. [9][10][11][12][22][23][24][25] However, previous studies were conducted at different sampling frequencies, and there is no evidence to suggest which sampling frequency and eye movement parameters are best suited for screening glaucomatous VFL during a free-viewing task. This study aimed to demonstrate how the sampling frequency of eye trackers influenced eye movement parameters in distinguishing glaucomatous visual field defects from those in healthy eyes.…”
Section: Discussionmentioning
confidence: 99%
“…However, they did observe smaller saccadic amplitudes and a restricted BCEA in the worse eye compared with the better eye. In a follow-up study, Asfaw et al 10 assessed eye movements in simulated VFL of varying degrees based on real glaucomatous VFL. They noted that saccadic amplitude and BCEA were reduced in the advanced VFL group compared with the no VFL group.…”
Section: Does the Sampling Frequency Of An Eye Tracker Affect The Det...mentioning
confidence: 99%
“…Asfaw et al ( 24 , 25 ) showed that the same patient displays differences in viewing behavior depending on with which eye they performed a free viewing task. The spread of fixation locations was smaller in the worse eye of glaucoma patients compared to the better eye ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…A set of features was extracted by kernel principal component analysis on a saccade map, and these features were used as the input of a Naïve Bayes classifier that separated the patients from the controls. Asfaw et al [37] simulated artificial VFDs from a real glaucoma patient and performed a free-viewing task using both images and videos. They evaluated the clinical usefulness of four eye-movement parameters by plotting receiver operating characteristics curves.…”
Section: Attempting Of New Assessment Methodsmentioning
confidence: 99%